Kindergarten Affordances for Physical Activity and Preschoolers' Motor and Social-Emotional Competence - Mariana Moreira; Guida Veiga; Frederico Lopes; Derek Hales; Carlos Luz; Rita Cordovil (MDPI AG, 2023)
This study examined the relationship between the quality of the kindergarten physical and social environment to promote physical activity (PA) and preschoolers' motor and social-emotional competence. Two Portuguese kindergartens (Gondomar city) were selected from a pool of seventeen with an assessment of kindergarten PA best practices (one with high PA practices, the other with low). Thirty-six children (M = 4.42; SD = 1.00 years) without neuromotor disorders participated in this study. Motor and social-emotional competence were assessed with standardized motor skills tasks and parent report of child behaviors. Children from the kindergarten with higher compliance with PA best practices showed significantly better motor competence. No statistically significant differences were found for social-emotional competence scores. These findings emphasize the critical importance of kindergarten in promoting preschoolers' motor competence by assuring a physical and social environment that enhances their PA practice. This is a particularly relevant concern for directors and teachers during the post-pandemic period, given the developmental delays and decreases in physical activity preschool children experienced across the pandemic period.